School-based staff development in two federal states in Germany. Issue 6 (10th August 2015) - Thillmann, Katja; Bach, Anabel; Wurster, Sebastian; Thiel, Felicitas
Abstract : Purpose: – In Germany up until now, there has been very little research on staff development in schools. The purpose of this paper is to comprehensively assess school-based staff development and to describe the interplay between different instruments of staff development (e.g. classroom observations, development discussions) at the school level. Design/methodology/approach: – Considering that different constellations of organizational management tools may be differentially effective in different contexts (see Mintzberg, 1983/1992), an approach that takes a combination of different staff development instruments into account was chosen. Data were gathered from principals of primary and secondary schools in two federal states of Germany. Using regression, cluster analysis, and analysis of variance, the authors examined different instruments and patterns of staff development used in everyday school practice and determined how these affected the professional development of teachers. Findings: – Five staff development patterns could be identified. With regard to the extent of professional development activities of teachers, these patterns have been proven to have a different impact. Furthermore, the use of the different staff development patterns seems to be heavily dependent on the type of school. Research limitations/implications: – Further research would be needed that examines if the three most relevant staff development patterns identified in this study can also be proven to be effective with regard to somewhat "harder" criteria than the extent of professional development activities of teachers. Such criteria could be teachers' teaching skills or even student achievement. Originality/value: – The current study is the first to examine staff development in German schools systematically. The results provide some good leads for further studies in this area.